Individual Responsibility to The Reconstruction of the Concept of Sovereignty in the Perspective of Rule of International Criminal Law (Халықаралық қатынастар және халықаралық құқық сериясы, 2023)
In recent years, the Afghanistan war and the Russian-Ukrainian war which have seriously threatened the stability of the international order have challenged the two mainstream theories of sovereignty, namely, “outdated sovereignty theory” and “absolute sovereignty theory”. The direct purpose of the rule of law is to stabilize and maintain order, establishing stable expectations for human activities. With the deepening development of the rule of law civilization and the establishment of the International Criminal Court, the concept of the rule of law has transcended regional limitations and formed a universal culture around the world. The concept of international rule of law and rule of international criminal law has been formed and established around the world. Individual criminal responsibility orders individual actors to jointly and severally bear the criminal responsibility in order to realize international fairness and justice, which is essentially a denial of state personality. Sovereignty theory should be interpreted in a new way from the perspective of rule of international law. Only by deconstructing the current “absolute sovereignty theory” and “sovereignty obsolete theory” and constructing a new theory of sovereignty that includes the content of “consensus and appropriate transfer of sovereignty by all countries” can there be room for the construction of the international rule of law, so that state power can be controlled by international laws, and national rights and international order can be better protected.Key words: individual responsibility, denial of state personality, rule of international criminal law, sovereignty